Adaptive step ODE algorithms for the 3D simulation of electric heart activity with graphics processing units. - Garcia-Molla, V M; Liberos, A; Vidal, A; Guillem, M S; Millet, J; Gonzalez, A; Martinez-Zaldivar, F J; Climent, A M (Computers in Biology & Medicine, 2014)
In this paper we studied the implementation and performance of adaptive step methods for large systems of ordinary differential equations systems in graphics processing units, focusing on the simulation of three-dimensional electric cardiac activity. The Rush-Larsen method was applied in all the implemented solvers to improve efficiency. We compared the adaptive methods with the fixed step methods, and we found that the fixed step methods can be faster while the adaptive step methods are better in terms of accuracy and robustness.